2014
DOI: 10.1378/chest.13-2702
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fluid Administration in the First Three Hours of Sepsis Resuscitation Is Associated With Reduced Mortality

Abstract: BACKGROUND:Th e surviving sepsis guidelines recommend early aggressive fl uid resuscitation within 6 h of sepsis onset. Although rapid fl uid administration may off er benefi t, studies on the timing of resuscitation are lacking. We hypothesized that there is an association between quicker, adequate fl uid resuscitation and patient outcome from sepsis onset time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 41 publications
(23 reference statements)
1
58
0
5
Order By: Relevance
“…30 Second, pneumonia is the most common cause of sepsis, a syndrome in which earlier, more aggressive care (more readily delivered in ICUs than the general ward) has been associated with reduced mortality. 31 Third, many studies, 3234 but not all, 35 suggest that ICU admission for pneumonia has been associated with increased rates of guideline-based treatment, which has been linked with improved mortality and reduced costs. Fourth, ICU admission increases the likelihood that a patient with pneumonia is managed by pulmonary or critical care specialists, clinicians whose case volume or expertise in pneumonia care may yield better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…30 Second, pneumonia is the most common cause of sepsis, a syndrome in which earlier, more aggressive care (more readily delivered in ICUs than the general ward) has been associated with reduced mortality. 31 Third, many studies, 3234 but not all, 35 suggest that ICU admission for pneumonia has been associated with increased rates of guideline-based treatment, which has been linked with improved mortality and reduced costs. Fourth, ICU admission increases the likelihood that a patient with pneumonia is managed by pulmonary or critical care specialists, clinicians whose case volume or expertise in pneumonia care may yield better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A hypotensive episode is associated with an increased risk of death, and the response to an adequate fluid challenge improves upon this discriminatory value for risk stratification (4043). Early fluid therapy targeted to endpoints is associated with a decrease in systemic inflammation, vasopressor use, and mortality and must be distinguished from late aggressive fluid therapy (24, 40, 44–48).…”
Section: Fluid Therapy—earlymentioning
confidence: 99%
“…Early fluid therapy targeted to endpoints is associated with a decrease in systemic inflammation, vasopressor use, and mortality and must be distinguished from late aggressive fluid therapy (24, 40, 44–48). Multiple studies have shown that the fluid challenge of 30 mL/kg fluid volume within 3 hours of presentation is associated with increased MAP, normalization of Sc vo 2 , and decreased vasopressor use at 6 hours.…”
Section: Fluid Therapy—earlymentioning
confidence: 99%
See 1 more Smart Citation
“…One relatively small study reported that in septic patients who received the same overall amount of fluid in the first 6 hours, there was a significant mortality difference in favor of the group that received a greater proportion in the first 3 hours. 11 Although the optimal timing of fluid bolus administration has yet to be clarified, it is unlikely that initiating intravenous fluid resuscitation as early as possible will cause harm. The picture is murkier with regard to the quantity of fluids to administer.…”
Section: Answermentioning
confidence: 99%